Nilai-Nilai Edukatif Dalam Surat Al Kautsar Beserta Implikasinya dalam Kehidupan (Tela’ah Tafsir Al Qurthubi) - Abid Nurhuda; Nur Aini Setyaningtyas (Social Science Studies, 2021)
slam is very concerned about education and its implementation which is based on the Qur'an and al-Hadith. So one of the words of God that contains educational teachings and contains educational values is the letter Alkautsar verses 1-3 (Tala'ah Tafsir Al Qurthubi). The purpose of this study is to find out the educational values of Islam contained in Surah Al-Kautsar verses 1-3 according to the interpretation of Jami' li Ahkami of the Qur'an by Al-qurthubi and to find out its implications in everyday life. The method used is library or library research with primary data sources namely Jami' Li Ahkami Al-qur'an and secondary data such as books, journals, articles and so on and then collected, processed then analyzed and concluded descriptively. So the conclusion obtained is that in the first paragraph there is an educative value of gratitude, namely acknowledging it with the heart, then saying it verbally and implementing/implementing it with the limbs. While the educational value in the second verse is spiritual value which is manifested in prayer worship (Hablun minAllah) and social value which is manifested in qurban worship (Hablun minannas). While the educational value in the third verse is the value of fighting spirit which is reflected in the good deeds of ma'ruf nahi mungkar and the value of toughness that is accompanied by responsibility, all of which are illustrated by that everyone will definitely get a reward according to their deeds.